Early neutrophil alveolitis after rechallenge in drug induced alveolitis. Issue 8 (August 1988) - Salmeron, S; Brochard, L; Rain, B; Herve, P; Brenot, F; Simonneau, G; Duroux, P
Abstract : A patient with drug induced alveolitis due to an antidepressant drug, nomifensine, is described. After an inadvertent rechallenge by the patient sequential bronchoalveolar lavage was carried out. Twenty four hours after the rechallenge the lavage fluid contained a high cell count with neutrophils predominating. Seven days after challenge the cells were predominantly lymphocytes.